Advanced pharmaceutical manufacturing: A functional definition. Issue 2 (10th January 2023) - Romañach, Rodolfo J.; Stelzer, Torsten; Sanchez, Eric; Muzzio, Fernando
Abstract: The term "Advanced Pharmaceutical Manufacturing" (APM) has become an ubiquitous buzzword with deep potential policy implications. There is a real danger that APM will be seen as a general panacea for solving economic woes and drug shortages, devoiding it from specific meaning, and depriving the technical community of focus much needed for its development and implementation. This paper first discusses several semantic definitions of APM that have been proposed in the field. A functional definition of APM is then presented as: A system that is designed using predictive models, where automation minimizes human intervention while enabling closed loop process control and real time quality assurance, where performance has been optimized to maximize desired process goals, where flexible amounts of product with equivalent attributes can be manufactured, and where equivalent processes can be implemented at multiple locations to manufacture products with equivalent critical quality attributes. The proposed definition is presented to motivate discussion and elicit contributions from other stakeholders, and to contribute to the development of a consensus framework for design, development, implementation, and evaluation of APM. Abstract : The term "Advanced Pharmaceutical Manufacturing" (APM) has become an ubiquitous buzzword with deep potential policy implications. A functional definition of APM is then presented as: A system that is designed using predictive models, where automation minimizes human intervention while enabling closed loop process control and real time quality assurance, where performance has been optimized to maximize desired process goals, where flexible amounts of product with equivalent attributes can be manufactured, and where equivalent processes can be implemented at multiple locations to manufacture products with equivalent critical quality attributes. The proposed definition is presented to motivate discussion and elicit contributions from other stakeholders, and to contribute to the development of a consensus framework for design, development, implementation, and evaluation of APM.